Photonics-Based RF Signal Phase Detector With Wide Operating Frequency Range and High Resolution - Hao Chen; Erwin H. W. Chan (IEEE Photonics Journal, 2021)
A new topology that generates a DC voltage whose value is depending on the phase difference of two input RF signals is presented. It is implemented by the mixer concept. With the use of microwave photonics, the mixer-based phase detector can be operated over a very wide frequency range. It also has the advantages of high phase detection resolution, small phase detection error, and small DC offset and phase offset. The phase detector can be constructed using off-the-shelf components including a single integrated optical modulator and a low-speed balanced detector. Measured results on the phase detector demonstrate a 0° to 180° RF signal phase difference detection range for 3.5 GHz to 18 GHz input RF signal frequencies, less than ±3° phase detection error and 2° phase detection resolution.